Penerapan prinsip authentic assessment pada pembelajaran matematika di sekolah dasar - Linda Nur Aini; Karsono Karsono; Siti Kamsiyati (Didaktika Dwija Indria, 2023)
In the learning process, assessment is crucial since it establishes students' differences from one another and their level of quality. Complete assessment will influence learning and serve as a guide for future policies. The precision with which evaluation principles are used will have a significant impact on validity and objectivity. In order to evaluate math learning in elementary schools, this study will look at how authentic assessment methods are applied. This study is a qualitative descriptive one. The subjects of the study were teachers, administrators, and students. In this study, interviews, observation, and document analysis were employed to obtain data. The Miles and Huberman model of interactive data analysis approaches is used in this study's data analysis method. Techniques for assessing the validity of data rely on a triangulation of sources, methods, and times. The findings of this research indicate that the principles of elementary school mathematics learning assessment are effective in realizing the authentic assessment concept.